KAJIAN STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI PESISIR SEI NAGALAWAN KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Mariany Siagian; Mohammad Basyuni; Rusdi Leidonald (AQUACOASTMARINE, 2015)
The purpose of research was to examine the condition and tourism potential in mangrove ecosystem area as foundation to develop mangrove ecosystem on Sei Nagalawan coastal according to ecotourism perception and environmental carrying capacity. This research was carried out in August-September 2014. The research method was purposive sampling for mangrove potential and SWOT analysis for developing strategies on mangrove ecotourism in Sei Nagalawan coastal area.. Mangrove species found were Avicennia marina, A. officinalis, Bruguierra cylindrica, and Rhizophora apiculata. Animals species found were birds, reptile, fish, mollusca and crustaceae. Tourism similarity index for mangrove ecosystem activity was 36 people/day. There were three priority strategies alternatively, firstly, to increase the bussiness management of mangrove ecosystem of ecoutorism activity. Secondly, to keep the tourism mangrove object by establising the carrying capacity area. Thirdly, to promote the mangrove ecotourism using internet or any medias.Keywords: Ecoutorism, mangrove ecosystem, Sei Nagalawan coastal, SWOT analysis.